1986
DOI: 10.1136/hrt.55.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Juxtaductal left pulmonary artery obstruction in pulmonary atresia.

Abstract: with pulmonary atresia associated with various other congenital anomalies in whom the central pulmonary artery originally gave rise to right and left pulmonary arteries. Twenty one patients who had not been treated surgically form the present study group. They range in age from 11 days to 21 years (median 4 years). Eight are males and 13 are females (Table). All were investigated by cross sectional echocardiography and angiocardiography. The morphology of the central pulmonary artery (pulmonary trunk and main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…Most congenital stenoses are the result of congenital heart disease with pulmonary undercirculation, such as tetralogy of Fallot, tetralogy of Fallot with pulmonary trunk atresia, and tricuspid valve atresia with pulmonary stenosis or atresia. Another type of congenital narrowing, especially in the left pulmonary artery, is due to coarctation formed at the site of insertion of the patent ductus arteriosus or ligamentum arteriosum, when some of the constricting tissue involves or encircles the pulmonary artery [11,12,30,34]. Branch pulmonary artery stenosis is a well-known feature of Williams syndrome [16,18], Alagille syndrome, and congenital rubella [10,57].…”
Section: Etiologymentioning
confidence: 99%
“…Most congenital stenoses are the result of congenital heart disease with pulmonary undercirculation, such as tetralogy of Fallot, tetralogy of Fallot with pulmonary trunk atresia, and tricuspid valve atresia with pulmonary stenosis or atresia. Another type of congenital narrowing, especially in the left pulmonary artery, is due to coarctation formed at the site of insertion of the patent ductus arteriosus or ligamentum arteriosum, when some of the constricting tissue involves or encircles the pulmonary artery [11,12,30,34]. Branch pulmonary artery stenosis is a well-known feature of Williams syndrome [16,18], Alagille syndrome, and congenital rubella [10,57].…”
Section: Etiologymentioning
confidence: 99%
“…half ventricle repair (1); bidirectional cavopulmonary shunt (4); and Fontan (2). Fourteen of the patients destined for biventricular physiology reached complete repair while 2 patients were still with shunts.…”
mentioning
confidence: 99%
“…Pulmonary arterial stenoses are often associated with other cardiovascular anomalies [19]. Momma et al [23], in an angiographic study, found nine cases of juxtaductal LPA stenosis and five cases of juxtaductal LPA atresia. Baum et al [1], in a clinicoradiologic study, reported 26 cases of pulmonary arterial branch stenoses.…”
Section: Discussionmentioning
confidence: 99%